Estimación del factor de reducción de fuerza sísmica para sistemas estructurales duales de edificaciones esenciales categoría A2 - Adauto Illanes, Benjamín Víctor (2024)
Seismic standards employ a seismic force reduction factor (R) to adjust elastic to inelastic design spectra, crucial for indicating ductility demand and determining the design basal shear force. Essential structures of category “A2”, such as hospitals, educational centers and barracks, must maintain their functionality after a significant earthquake. In seismic zones Z4, Z3 and Z2, these structures, of low height and with periods less than 0.5s, use dual systems with a factor R=7 (MVCS, 2018). However, these buildings, although rigid and low ductility, have a high seismic reduction factor. This study seeks to estimate the R factor for essential structures “A2” and associate these factors with ductility levels. For this, 74 regular structures were evaluated with drifts less than 0.007 and shear forces in walls between 20% and 80% of the basal shear. The ductility reduction factor for one degree of freedom systems (Rμ1GDL) was calculated using the gamma hysteresis model (Lestuzzi & Badoux, 2003). RΩ and RY factors were obtained through nonlinear static analysis (Pushover), and RμVGDL factors were determined with nonlinear time history analysis. The reinforced concrete design and nonlinear analyzes were performed in Opensees v2.5.0 software, and Matlab R2017b was used for the seismic demand. The results indicate that the R factor for dual structural systems of essential buildings category A2, with periods of 0.12s to 0.34s and ductilities of 2 to 4, varies between R=1.10 and R=2.11, suggesting that they should be designed for seismic forces greater than the currently required.